2014
DOI: 10.12968/bjnn.2014.10.4.191
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and meeting people's post-stroke emotional needs: a service evaluation

Abstract: Background: Post-stroke emotional needs were highlighted as going unmet in a recent report by the Stroke Association. Aim: To determine local service provision of emotional support. Method: Questionnaires were distributed to 200 stroke patients and their carers. The survey aimed to gather information on emotional needs post-stroke and the service people had received. Results: A total of 88 sets of questionnaires were returned by post. Some 47% of patients and 35% of carers/relatives felt that their emotional n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Self-determination theory in healthcare suggests the provision of basic psychological needs for patients post stroke has the potential to improve patient's autonomy and wellbeing (Deci & Ryan 2012). The literature has reported that patients post stroke are unaware that HCPs can provide such support and suggests that due to HCPs lack of selfconfidence in the assessment and management of psychological issues, discussions with patients is avoided (Platten 2014, Harrison et al 2017. With this in mind, this review examines HCPs knowledge, experiences, and perceptions of the provision of psychological care to patients post stroke and to make recommendations for future practice, education, policy and research.…”
Section: Introductionmentioning
confidence: 99%
“…Self-determination theory in healthcare suggests the provision of basic psychological needs for patients post stroke has the potential to improve patient's autonomy and wellbeing (Deci & Ryan 2012). The literature has reported that patients post stroke are unaware that HCPs can provide such support and suggests that due to HCPs lack of selfconfidence in the assessment and management of psychological issues, discussions with patients is avoided (Platten 2014, Harrison et al 2017. With this in mind, this review examines HCPs knowledge, experiences, and perceptions of the provision of psychological care to patients post stroke and to make recommendations for future practice, education, policy and research.…”
Section: Introductionmentioning
confidence: 99%